Development of Web-Based Learning Media in Vocational Secondary School - Hendra Dani Saputra; N. Nasrun; W. Wakhinuddin (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This research aims to develop a Web-based learning media effectively on subjects of Automotive Basic Electrical Engineering in Vocational Secondary School (SMK) Negeri 1 Lintau Buo. Web-based learning media developed measured their effectiveness, as one media choice efficient and effective learning for students This research using the method of Research and Development (R&D) with 4-D model (Define, Design, Develop, and Disseminate). The results obtained from this research are as follows: (1) the learning media validity of the web-based learning media is declared valid with value of 85.99%, and on aspects of the material declared valid with a value of 87.7%; (2) the media practicalities of web-based learning media on the teacher's response stated the practical value of 81.7%, and based on the response of the students stated the practical value of 88%; (3) the media effectiveness of the web-based learning media was declared effective in improving student learning outcomes.